Presentation zen : simple ideas on presentation design and delivery - Reynolds, Garr (Voices that matter, 2012)
"Garr Reynolds, author of the best-selling book on presentation design and delivery with over 150,000 copies sold, is back with this newly revised edition of his Classic book, Presentation Zen. Showing us there is a better way to reach the audience through simplicity and storytelling, Garr tackles the conventional wisdom of making "slide presentations" and shares his approach to designing and delivering successful and provocative presentations. In this new edition, Garr includes fresh examples from which to draw inspiration, and offers techniques for cutting through the noise and distractions of modern life and truly engaging with your audiences in ameaningful way. Combining the solid principles of design with the tenets of Zen simplicity, Presentation Zen, second edition, puts you solidly on the path to creating simpler, more effective presentations that will be appreciated, remembered, and best of all, acted upon". -- Back cover